Dinamika Perang Suriah: Aktor dan Kepentingan - Syarif Bahaudin Mudore; Nurlaila Safitri (UIN Mataram, 2019)
This article examines actors in the Syrian civil war 2011-2019. The involvement of the super power states give some reasons of complexity in the Syrian civil war. Exactly, they have national interests that they protected during the war. Besides of that, this article proposed the main interests that found in this war. National interests and hegemony strategies played by foreign actors signify the strength of economic ambitions, especially weapons and oil business, and political power transactions. The theory of hegemony and national interests is positioned as a knife of analysis to identify the interests and motives of the involvement of state actors in Suriah conflicts. This research pursues the conclusion that both state actors who are pro-regime or not remain on the same frequency: seizing influence.